Health Poverty Alleviation Project in Rural China: Impact on Poverty Vulnerability, Health Status, Healthcare Utilization, Health Expenditures - Li Z; Chen Y; Ding J (Dove Medical Press, 2023)
Zhipeng Li,1 Yuqian Chen,2 Jing Ding3 1Qu Qiubai School of Government, Changzhou University, Changzhou City, People's Republic of China; 2School of Economics and Management, Shanghai University of Political Science and Law, Shanghai, People's Republic of China; 3School of Public Economics and Administration, Shanghai University of Finance and Economics, Shanghai, People's Republic of ChinaCorrespondence: Yuqian Chen, Affiliated School of Economics and Management, Shanghai University of Political Science and Law, No. 7989 Waiqingsong Road, Qingpu District, Shanghai, 201701, People's Republic of China, Tel +8618502116053, Fax +862139227342, Email yvqianc@163.comBackground: China has lead to the inception of the Health Poverty Alleviation Project (HPAP) in 2015. While the previous studies suggest that, despite its apparent reduction in patients' financial strain, the long-term poverty reduction effects are yet to be fully elucidated. This study explores HPAP's enduring impact on poverty reduction and the potential moral hazards.Methods: Data were obtained from four waves of the China Health and Retirement Longitudinal Study (CHARLS) spanning 2011- 2018. We employed difference-in-differences (DID) models to gauge HPAP's influence on participants' poverty vulnerability, health outcomes, and healthcare utilization. The dynamic DID model is employed to test the robustness of HPAP policy effects. The mediation effect models were used to understand HPAP policy outcomes through physical examinations and inpatient care.Results: Our dataset encompassed 40,384 participants, of which 5946 (14.72%) had been exposed to HPAP and 34,438 (85.28%) had not access. Our findings reveal that HPAP decreases poverty vulnerability by 3.3% (p < 0.01) and attenuates health deterioration by 1.84% (p < 0.01). Furthermore, HPAP enhances inpatient care utilization by 9.34% (p < 0.01) and self-treatment behaviors by 4.1% (p < 0.01) while significantly slashing outpatient and inpatient expenses (p < 0.05). The implementation of HPAP has significantly reduced healthcare costs by 72.8% (p < 0.05) out-of-pocket (OOP) payments of outpatient care during the past month for the last time, and 89.39% (p < 0.05) out-of-pocket (OOP) payments of inpatient care during past the year for the last time. Mechanistic analyses have shown that the indirect effect of the HPAP policy decreases poverty vulnerability by − 0.132% (p < 0.05) physical examinations and − 0.309% (p < 0.05) inpatient care.Conclusion: The HPAP initiative markedly attenuates poverty vulnerability and forestalls health decline among the rural populace. Moreover, HPAP bolsters healthcare service use, such as physical examinations and inpatient care, primarily attributed to the release of pent-up demand rather than moral hazards. Keywords: chronic poverty, poverty due to illness, poverty vulnerability, ex ante moral hazard, ex post moral hazard, health poverty alleviation project